Craniofacial parameters and obstructive sleep apnea in newly diagnosed acromegaly - Pilarska, Magdalena; Dżaman, Karolina; Szczepański, Dawid; Węgrzecki, Tomasz (Frontiers in Endocrinology, 2025)
IntroductionAcromegaly is a rare condition caused by excess growth hormone after skeletal maturity, leading to abnormal soft tissue and bone growth. These changes raise the risk of obstructive sleep apnea (OSA) due to craniofacial abnormalities.ObjectiveThe study aims to determine the correlation between the occurrence and severity of OSA and craniofacial anthropometric parameters in patients with newly diagnosed acromegaly.Study designObservational, cross-sectional study.SettingSingle-center study involving patients diagnosed with acromegaly.MethodsThe research included 30 patients ranging from 25 to 81 years old (mean age 48) who were diagnosed with acromegaly. The diagnosis of OSA relied on polygraphy with the SOMNO check micro device. MRI provided the necessary craniofacial and upper airway measurements. Each patient received an ear, nose, and throat examination followed by a fiberoptic evaluation of the upper airway.ResultsOSA was diagnosed in 76.67% of patients. The analysis revealed that moderate to severe OSA affected 46% of patients, while women developed the condition at twice the rate of men. The research established a statistically relevant link between the severity of OSA and tongue base hypertrophy. The study failed to detect meaningful relationships concerning OSA severity and palatine uvula hypertrophy on MRI and between OSA severity and palatine tonsil size and middle pharyngeal airway width.ConclusionOur study found a high OSA prevalence (76.67%) in newly diagnosed acromegaly patients and a significant association between tongue base hypertrophy (FTP scale) and OSA severity (p < 0.001), while other anatomical parameters showed no significant correlation with AHI. The high prevalence of OSA in patients with newly diagnosed acromegaly highlights the importance of including sleep apnea screening in the initial diagnostic workup.